Synovial fluid-derived exosomal lncRNA PCGEM1 as biomarker for the different stages of osteoarthritis - Zhao, Ye; Xu, Juan (International orthopaedics, 2018)
Objects The purpose of this study is to investigate the role of exosomal lncRNAs from plasma and from synovial fluid in patients with osteoarthritis (OA) and to determine their diagnostic value in distinguishing the early stage of OA from progressive stage of OA. Methods Participants were divided into three groups. The control  group included 20 pre-arthritic patients, early OA group included 20 patients in the early OA, and late-stage OA group included 22 patients in the late-stage OA. For all subjects, blood sample from cubital vein and synovial fluid sample from knee joint were collected. Exosomes were extracted by ultracentrifugation. LncRNAs were extracted from exosomes using RNeasy kit, and the expression of several exosomal lncRNAs, including HOTAIR, PCGEM1, and GAS5, was measured using quantitative real-time polymerase chain reaction (qPCR). Also, Spearman’s correlation test was performed to determine the correlation between exosomal lncRNA PCGEM1 and WOMAC index. Last, the receiver operating characteristic (ROC) curve was performed to determine the diagnostic value of exosomal lncRNA PCGEM1 in distinguishing the different stages of OA. Results First, for plasma, both the expression of exosomes in three groups and the relative expression of exosomal lncRNAs chosen showed no significant difference among three groups, while for synovial fluid sample, the expression of exosomes in early OA and late-stage OA was much markedly higher than that in controls; and the expression of exosomal lncRNA PCGEM1 was markedly higher in late-stage OA than in early OA, and markedly higher in early OA than controls. Both the expression of exosomal lncRNA HOTAIR and GAS5 showed no significant difference among these groups. Second, there was a positive relationship between exosomal lncRNA PCGEM1 and WOMAC Index. Last, ROC curve showed that the area values under the curve of exosomal lncRNA PCGEM1 were 0.879, 0.757, and 0.593, respectively. Conclusion Our study demonstrated that exosomal lncRNA PCGEM1 might be a powerful indicator in distinguishing the early OA from the late-stage OA.